Effect of particle intrusion on rail seat load distributions on heavy haul freight railroads. Issue 2 (2nd April 2016) - Greve, Matthew J.; Dersch, Marcus S.; Edwards, J. Riley; Barkan, Christopher P.L.; Mediavilla, Jose; Wilson, Brent
ABSTRACT: The rail seat load distribution is critical for analysing failure mechanisms associated with rail seat deterioration (RSD), the degradation of concrete surface at the sleeper rail seat. RSD can lead to wide gauge, cant deficiency, and an increased risk of rail rollover. Previous experimentation with matrix-based tactile surface sensors (MBTSS) at the University of Illinois Urbana-Champaign (UIUC) has yielded concern regarding the feasibility of crushing of the concrete material at the rail seat. This paper examines data collected from laboratory experimentation in which the particle size, particle intrusion, vertical rail seat load, and lateral over vertical force ratio were varied to generate extreme loading environments. No pressures exceeded the concrete compressive strength. However, certain loading scenarios yielded pressures exceeding the concrete fatigue strength. It was therefore concluded that accumulated crushing damage due to a high number of repeated load applications is a feasible failure mechanism of RSD initiation.